Encontro de encontros: investigando a atividade de trabalho de operadores de caixa e empacotadores - Dártora, Tamires (2014)
This research aims to investigate the work activity of cashiers and packers from Federzoni supermarket, located in Caieiras - SP, in order to demonstrate that such activities are not only mechanical operations , they are more complex than we have become accustomed to consider. Therefore, we used the assumptions of French Discourse Analysis, mainly supported by the work of Dominique Maingueneau, and assumptions of the ergological approach, articulating the concepts of work activity, and good non adherence in the first chapter; the infidelity of the institucional environment and the discursive ethos in the second chapter, and speech genres , discursive memory and non-neutrality of prescripts in the third chapter, continuously targeted by the principle of semantic constraints system, as proposed by Maingueneau (1984/2008). For this research, we proposed the methodology we called double anticipation: at first, we investigate the history of a work activity requirements and, as a second step, the approach of the workers and the completion of that activity, always considering that there is a constant back and forth between these two poles, since the work activity is the knot that binds them, puts them in relationship. Thus, in addition to show certain peculiarities that we cannot anticipate, which makes the work activity of cashiers and packers even more complex than is generally treated, we reflect on the activity of the researcher in a research activity job